Direct channeling of mosque institution fund in financing waqf projects: accepted or declined? - Muhammad, Fidlizan; Abdul Razak, Azila; Hussin, Mohd Yahya; Awang, Salwa Amirah; Saad, Ram Al Jaffri (Advance Scientific Research, 2020)
Mosque is a religious institution which receives constant financial support from the Muslim community in order to carry out various development projects and spiritual activities. However, the expenditure of mosque institution is limited to the development for the benefit of the parishioners only. Moreover, the existence of waqf development institution faces the problem of funding constraint that causes the inability to complete the construction of development projects. Therefore, this study aims to identify acceptance factors of Muslim Community towards the direct involvement of mosque institution to channel some part of monetary contribution from the Muslim society, at the community level, for waqf development outside the community. This study has employed the instrument of a questionnaire form involving 312 Muslim respondents in one state of Malaysia and logistic regression was used for the analysis. The results show that knowledge, equipment, money and difference are positively significant whereas satisfaction show negative direction towards the agreement to transfer mosque fund to waqf fund. In general, the finding of the study provide supports that respondents agree to channel the mosque institution fund for the use of development outside of the community. Interestingly, respondents are found to be open minded in the matter of mosque fund expenditure to be utilized for the waqf development even though it will be implemented in the area of outside of the community. Nevertheless, this perception is influenced by the current level of development of a mosque encompassing the physical facilities, infrastructure and activities conducted by the mosque management. The physical level of the mosque which has yet to reach certain quality requires that the mosque fund to be spent first on its own community needs. Thus, this study shows that Muslim community does support the involvement of mosque institution as the agent in the development of economy and social by utilizing the mosque fund.